Comparative Study on Problem Based Learning against Conservative Learning Method among Undergraduate Medical Students - S.P., Jai Prabhu; K. , Prabhu; Karunakaran, Balaji; Maria Francis, Yuvaraj (International Journal of Psychosocial Rehabilitation, 2020)
Problem-based learning (PBL) has been found to be an effective tool for lifelong learning. PBL and routine lectures are different in so many ways, as PBL requires active participation of the students. In PBL, the problem has to be analyzed by the student(s) himself, and then it has to be understood, and he has to find a solution to the problem, which will eventually improve the cognitive ability and thought processes of the students. The medical stream is different from others in that, in this field, professionals have to develop lifelong learning habits. Moreover, to become a successful doctor, one should develop the skills to integrate the basic medical sciences with the clinical subjects. Through PBL, lifelong learning can be accomplished, and it can be an effective tool. PBL is different from routine lectures as it makes the students participate actively. The aim of this study is to analyze the validity of problem-based learning (PBL) as a teaching tool and the perceptions of the students. Phase I MBBS students, 150 in total, have voluntarily participated in the study. All the students were randomly divided into 10 groups, with each group having one teaching faculty member in charge. Before and after each PBL session, a multiple-choice question (MCQ) test was conducted. Along with regular teaching, most of the students preferred to have PBL. The favorable response, acceptability, and positive impact on the students made us continue using more PBL sessions. Further, conducting workshops on PBL may help the medical faculties who are all involved in curriculum development to consider PBL to be incorporated in the medical curriculum, since it can have a positive impact on the process of learning. And the implementation of PBL in the medical curriculum requires a greater number of multicenter studies that can establish the need for PBL and its benefits in the teaching process of student populations.